Effects of sodium roasting on the leaching rate of boron-bearing tailings and its mechanism analysis. Issue 8 (8th August 2018) - Zou, Chengxi; Tang, Zhenyu; Xie, Wei; Fu, Hanguang; Kuang, Jiacai; Deng, Yingjun; Cao, Taishan
Abstract : The study reported was intended to improve the leaching rate of boron-bearing tailings, using a method of sodium roasting that uses boron-bearing tailings as the raw material and Na2 CO3 as the sodium agent. The effects of the roasting temperature and Na2 CO3 amount on the leaching rate of boron-bearing tailings are mainly evaluated. The morphology and composition of the samples after sodium roasting are analysed by scanning electron microscopy and X-ray diffraction. The results show that sodium roasting can significantly improve the leaching rate of boron-bearing tailings. Under the optimal conditions where roasting temperature is 950°C, Na2 CO3 amount is five times the theoretical amount and roasting time is 2 h, the leaching rate of boron-bearing tailings is up to 86.78%. Based on the analysis of the characterization results and the mechanism analysis of the sodium roasting process, the main reason for the increase of leaching rate is the reaction between Na2 O produced by the decomposition of Na2 CO3 and the boron in boron-bearing tailings resulting in soluble sodium borate. The results provide a scientific basis for the efficient comprehensive use of boron-bearing tailings.